007 Exploring perceptions of consanguinity in women from an east london community: analysis of discussion groups. (December 2018) - Cupp, MA; Adams, M; Heys, M; Lakhanpaul, M; Alexander, E; Peachey, M; Manikam, L
Abstract : Background: Consanguinity refers to relationships between blood relatives. Consanguineous relationships are prevalent in many parts of the world, especially in South Asian and Middle Eastern populations with particularly high prevalence in those of Asian Pakistani descent. There are potential health risks associated with consanguinity due to the increased risk of children with consanguineous parents being diagnosed with an autosomal recessive genetic disorder. This study explores perceptions of consanguinity by reporting the experiences and opinions of women in an ethnically diverse community in London. Methods: An estimated 200 women living in the London Borough of Newham were approached by a community facilitator through selective sampling and invited to attend a discussion group on consanguinity as part of a qualitative study. Field notes from four group discussions were coded manually to derive common themes for thematic analysis. Results: 36 women attended, of whom 56% identified as Asian Pakistani (n=20). The identified themes included (1) wide variation in participants' views of consanguinity and associated health risks, (2) the value of informed decisions and (3) preferences for information distribution (figure 1). Although participants had diverse opinions on consanguineous marriages with variation in awareness, awareness of risks was favoured and thought to be central to educated decision making. Participants were in favour of structured education on genetic literacy for children, with the aim of ensuring everyone is able to make informed decisions regarding consanguinity. Conclusion: Identified themes highlight the importance of involving the community in efforts to increase awareness around consanguinity and genetic risk. This study emphasises the need for awareness and education to enable informed decisions regarding consanguinity and the value of co-developing educational efforts with the community in light of variation in views and values. We recommend further engagement through focus groups to inform the provision of information on consanguinity in local communities.